A fuzzy logic enhanced bargaining model for business pricing decision support in joint venture projects - Yan, Min-Ren (Journal of Business Economics and Management, 2011)
Project businesses are increasingly emerging and many companies cooperatively participate in various projects by the manner of joint venture (JV) for creating synergistic competitiveness. In a project-based short-term JV, the project tasks of JV parties can be properly allocated based on complementary specialties but the rewards sharing is always a challenge in the bargaining process. For improving the manager's reasoning process of pricing decisions, this paper incorporates game theory and fuzzy set theory for the development of a bargaining model, which can be used to estimate acceptable prices for JV parties in accordance with each party's costs and each party's need for the project's revenue. The proposed decision support model can assist JV companies to understand their bargaining positions and select a bargaining strategy in a systematic and rational manner. Irrational offers and alternatives can also be detected and eliminated during the dynamic bargaining process, so as to maintain right businesses.Article in English.Fuzzy loginio pasikeitimų vertinimo metodo taikymas jungtinės veiklos projektų vertei nustatytiSantrauka. Verslo projektai savo dydžiu, tematika, pobūdžiu ir kitais aspektais nuolat kinta, todėl dauguma kompanijų, siekdamos išlaikyti konkurencinį pranašumą bei rengdamos įvairius projektus, jungiasi į tam tikras jungtines įmones, kurios vykdo jungtines veiklas, skirtas tik tam projektui įgyvendinti. Tokios įmonės, kurios apribotos projekto trukmės, įgauna tam tikrų savybių, kai tikėtina nauda iš šio susijungimo yra neapibrėžta ir nuolat kinta. Šio straipsnio autoriai, siekdami pagerinti motyvacinę vadovų sistemą, priimdami sprendimus dalyvauti jungtinėje veikloje ir įvertindami priimtiną santykį tarp investuojamos sumos dydžio ir tikėtinos naudos, taiko žaidimų teoriją bei Fuzzy metodą.Reikšminiai žodžiai: derybos, vertinimas, sprendimų priėmimas, jungtinės veiklos įmonė, strateginis susivienijimas, žaidimų teorija, Fuzzy metodas.